Pendampingan Usaha Mikro Kecil dan Menengah Dalam Meningkatkan Kualitas Produk Pada UMKM Kelurahan Gudang Kota Bogor - Zuhdi, Saefudin; Sukartaatmadja, Iswandi; Argoputro, Stanislaus Bandung (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
ABSTRACTProblems that occur in home industries or Micro, Small and Medium Enterprises (MSMEs) in Bogor City revolve around product quality. Awareness of maintaining product quality, there are several factors that determine product quality, including products that are clean in terms of materials and processes (hygienic), product safety (not using chemical materials and dyes), product appearance, and product packaging. The solution provided is providing assistance, in the form of counseling and training, to MSMEs in Bogor City is to increase the empowerment of partners according to the problems faced by MSMEs, namely increasing the knowledge and skills of MSME actors. Likewise, the number of products, production capacity, number of assets, total turnover, and management capabilities have increased. The planned activities that will be carried out are assistance and training on quality production. The aim of this activity is for MSME players to increase their knowledge and skills. The results obtained by MSME players are products that are fit for distribution, products can be marketed widely, product safety is guaranteed, and buyer confidence increases. Keywords: Product Quality, Product Innovation, SMEs